Natural killer cell activity in coeliac disease: effect of in vitro treatment on effector lymphocytes and/or target lymphoblastoid, myeloid and epithelial cell lines with gliadin - Castany, M A; Nguyen, H H; Pospísil, M; Fric, P; Tlaskalová-Hogenová, H (Folia microbiologica, 1995)
To analyze the possible involvement of natural killer (NK) cell activity in the pathogenetic mechanism of coeliac disease (CD) we measured the spontaneous cytotoxic cell activity of peripheral blood mononuclear cells (PMNC) from patients with CD and from healthy donors. No significant differences were found between the NK cell activity of PMNC from healthy donors and from patients with CD using a standard 51 Cr release assay. However, a 30-min treatment of PMNC with gliadin inhibited NK cell activity in patients with CD. On the other hand, a 1-d incubation with gliadin induced cytotoxic cell activity of PMNC against the NK-resistant target cells such as the epithelial HT-29 and the lymphoblastoid RAJI cell lines, suggesting that activation of PMNC by cultivation with gliadin can occur.
Keywords: Cytotoxicity, Immunologic; Humans; Lymphocytes; Tumor Cells, Cultured; lymfocyty; dítě; Child; dospělí; lidé; Cells, Cultured; buňky NK; nádorové buňky kultivované; Killer Cells, Natural; Adult; gliadin; celiakie; kultivované buňky; Gliadin; cytotoxicita imunologická; buněčná cytotoxicita závislá na protilátkách; Antibody-Dependent Cell Cytotoxicity; Celiac Disease